PENGARUH JUMLAH PENDUDUK DAN PENDAPATAN DOMESTIK REGIONAL BRUTO (PDRB) TERHADAP KEMISKINAN DI KABUPATEN KUANTAN SINGINGI - Novri Silastri; Rita Yani Iyan; Lapeti Sari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research was conducted in Kuantan Singingi Regency and aimed to find out the influence of sum of citizens and Gross Regional Domestic Income toward poverty in Kuantan Singingi Regency. The analysis was using linear bifilar regression analysis. This research used time data series from 2003 – 2013 which are poverty as dependent variable and Gross Regional Domestic Income as independent variable. From the research finding it was found out that R was 0.933 which indicated that there was positive connection between independent variable (Gross Regional Domestic Income) toward dependent variable (poverty). The result of the calculation was R20..916 which meant the fluctuation of poverty was influenced by the sum of the citizens and Gross Regional Domestic Income by 91.6%. The rest is influenced by some factors beyond this research. The value of variable regression was 0.046. It meant if other variables were static, then if there wasan increase of 1.000 citizens, it will be able to reduce poverty up to 4.6%. On the other side the regression coefficientof the variable of Gross Regional Domestic Incomewas as big as -0.007. It meant when the other variables were static , then if there was an increase up to 1.000 on the sum of the citizens it could decrease the poverty up to 7%.Keywords : Sum of Citizens, Gross Regional Domestic Income, and Poverty